2017
DOI: 10.21608/jpp.2017.40871
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Some Natural Products As an Alternative Chemical Growth Regulators on Rooting Response‚ Growth and Chemical Composition of Rosemary Cutting

Abstract: This study was conducted at the Experimental Station and Laboratory of Vegetable and Floriculture Department, Fac. of Agric., Mansoura Univ., Egypt, during 2015/2017 seasons to investigate the effect of some natural products and some alternative chemical growth regulators on rooting response‚ growth and chemical composition of cuttings of rosemary (Rosmarinus officinalis L.) plants. The layout of the experiment was completely randomized block design (CRBD) with three replications. The obtained results could b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
3
2
0
1
Order By: Relevance
“…Overall, the individual treatments of seaweed extract and coconut water were more effective in increasing the rooting percentage than IBA or A. rhizogenes alone. These findings are in agreement with those reported by Kasem and Abd El-Baset(2014), Pacholczak et al (2016), Massoud et al (2017), Sarmast et al (2019), Ibironke (2019) and Dada et al (2019), who revealed that treating cuttings with biostimulants enhanced the rooting percentage compared to untreated or IBAtreated cuttings. On the other hand, application of seaweed extract as drench surpassed those of seaweed extract treatments as spray.…”
Section: Rooting Percentagesupporting
confidence: 93%
See 2 more Smart Citations
“…Overall, the individual treatments of seaweed extract and coconut water were more effective in increasing the rooting percentage than IBA or A. rhizogenes alone. These findings are in agreement with those reported by Kasem and Abd El-Baset(2014), Pacholczak et al (2016), Massoud et al (2017), Sarmast et al (2019), Ibironke (2019) and Dada et al (2019), who revealed that treating cuttings with biostimulants enhanced the rooting percentage compared to untreated or IBAtreated cuttings. On the other hand, application of seaweed extract as drench surpassed those of seaweed extract treatments as spray.…”
Section: Rooting Percentagesupporting
confidence: 93%
“…On the contrary, the minimum rooting percentage was recorded with untreated basal cuttings (2.5%). These results are in parallel to those obtained by Mohamed et al (2014) and Massoud et al (2017), showed that treating tip cuttings with IBA and/or biostimulants led to increase rooting percentage comparing with the untreated cuttings for Conocarpus erectus and Rosmarinus officinalis, respectively.…”
Section: Rooting Percentagesupporting
confidence: 89%
See 1 more Smart Citation
“…These results align with those of [41] on Zanthoxylum aramatum, who reported that the control set of branch cuttings had not produced any roots. Also, tip cuttings treated with IBA increased the rooting percentage compared with the untreated cuttings for Conocarpus erectus and Rosmarinus officinalis, respectively [42][43][44].…”
Section: Resultsmentioning
confidence: 99%
“…Media tanam yang digunakan adalah tanah hitam dan arang sekam padi dengan perbandingan 1:1 (Suryanto et al 2012). Stek yang sudah disiapkan direndam selama 2 jam (Massoud et al 2017) Berdasarkan pengamatan terhadap munculnya akar dan tunas menunjukkan persentase pembentukan akar dan tunas 0% untuk semua perlakuan pada stek daun jambu bol. Hasil ini menunjukkan bahwa perlakuan air kelapa belum mampu memacu pembentukan akar dan tunas sampai 50 hst.…”
Section: Tahapan Penelitianunclassified